2003
DOI: 10.1038/nn1009
|View full text |Cite
|
Sign up to set email alerts
|

Identification and function of thermosensory neurons in Drosophila larvae

Abstract: Although the ability to sense temperature is critical for many organisms, the underlying mechanisms are poorly understood. Using the calcium reporter yellow cameleon 2.1 and electrophysiological recordings, we identified thermosensitive neurons and examined their physiologic response in Drosophila melanogaster larvae. In the head, terminal sensory organ neurons showed increased activity in response to cooling by < or =1 degrees C, heating reduced their basal activity, and different units showed distinct respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
153
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(167 citation statements)
references
References 28 publications
6
153
1
Order By: Relevance
“…Sayeed and Benzer [30] found that when adult flies are placed upon a linear thermal gradient (18 to 31.5°C), these animals show a strong preference for ~24° C. However, unlike nematodes, flies cultivated or acclimatized at temperatures either above or below 24°C (29 or 18° C) still retain this partiality and thus do not reset their preferences based upon experience. Moreover, in a two-temperature choice paradigm, adult flies prefer 22 over 30° C. Similarly, Liu et al [31] showed that Drosophila larvae prefer to reside at 18°C when given the choice of this temperature versus either 11 or 30°C. In another experimental paradigm, larvae placed upon a thermal gradient from 27 to 41°C were shown to thermotax to the coolest temperatures, avoiding those above their optimal growth temperature [32].…”
Section: Thermotactic and Thermosensory Behaviors In Drosophilamentioning
confidence: 90%
See 4 more Smart Citations
“…Sayeed and Benzer [30] found that when adult flies are placed upon a linear thermal gradient (18 to 31.5°C), these animals show a strong preference for ~24° C. However, unlike nematodes, flies cultivated or acclimatized at temperatures either above or below 24°C (29 or 18° C) still retain this partiality and thus do not reset their preferences based upon experience. Moreover, in a two-temperature choice paradigm, adult flies prefer 22 over 30° C. Similarly, Liu et al [31] showed that Drosophila larvae prefer to reside at 18°C when given the choice of this temperature versus either 11 or 30°C. In another experimental paradigm, larvae placed upon a thermal gradient from 27 to 41°C were shown to thermotax to the coolest temperatures, avoiding those above their optimal growth temperature [32].…”
Section: Thermotactic and Thermosensory Behaviors In Drosophilamentioning
confidence: 90%
“…Like in C. elegans, peripheral sensory neurons in larvae have been mapped anatomically and structurally and can be observed optically as they lie at the surface of the semi-transparent cuticular layer [31]. Sensory neurons fall into two classes: type I, which terminates in a single ciliated dendrite, and type II, which lack sensory cilia and extend multiple dendrites [23].…”
Section: Neuronal Substrates For Thermosensationmentioning
confidence: 99%
See 3 more Smart Citations